Exploring Trust Dynamics in the Labour Market: A Behavioural Economics Perspective - Bakir-Yildirim, Zeynep Sumeyra; Cakmak-Sahin, Senem (SOSYOEKONOMI SOC, 2026)
This study explores the dynamics of trust in the labour market from a behavioural economics perspective, utilising data from the World Values Survey. We examine how employment status, job-related concerns, and perceptions of corruption influence trust. Our findings indicate that full-time employment and high income levels lower trust, whereas perceptions of corruption intensify this effect. The study recognises limitations, including incomplete representation of informal jobs and variation in income-reporting practices. It highlights the complex interaction of factors that shape trust within the labour market. The uniqueness of this research lies in conceptualising trust as a multifaceted construct, including cognitive expectations, mental shortcuts, and emotional dispositions. The study contributes to the understanding of trust in the labour market and its links with factors such as employment levels, job concerns, and perceptions of corruption. It enriches the literature by emphasising the complex interplay between cognitive and emotional factors in shaping trust in labour markets. Future research should investigate non-standard working patterns, including informal, flexible, and atypical employment, as well as the influence of cultural structures within cultural codes.
Keywords: Behavioural Economics; Trust; Labour Market; WVS; GENERALIZED TRUST; SOCIAL TRUST; PSYCHOLOGY; CORRUPTION; DISTRUST; STATE; WORK; Business & Economics